Understanding the Culture of Research Collaboration: An Exploration of Transnational Partnerships - Rambur, Betty (My University, 2009)
Global partnerships with multi-national teams are increasingly referenced as a means to approach the world?s most pressing problems. This interactive session details an empirically derived conceptual framework that describes seven distinct types of inter-institutional, multinational research partnerships along a range of increasing faculty risk, decreasing stability, increasing human factors with compounding interaction costs, and increasing time to research outputs. Participants will critique the framework and discuss applications and implications in reference to their fields and institutions. This presentation is part of the Ideas and Universities International Video Seminar Series. The program theme for the spring 2008 semester is "Universities as Organizations: Looking Inwards, Looking Outwards."
Keywords: International and Comparative